Peran Sikap Orang Tua Terhadap Pencegahan Diabetes Melitus Anak di Kecamatan Jatilawang - Dani Amelia; Zahra Aminy Tanjung; Safitri Safitri; Naila Rukhil Azizah; Lu’lu Nafisah (Jurnal Sehat Mandiri, 2025)
Diabetes mellitus is the third leading cause of mortality in Indonesia. According to the Indonesian Pediatric Society (IDAI), there were 1,220 reported cases of diabetes in children in 2018. As of 2023, this number had increased by 70% compared to 2010. The highest incidence in the Banyumas District was recorded in the Jatilawang Subdistrict. Various factors contribute to the rising number of diabetes cases among children, with parents playing a crucial role in implementing preventive behaviors. Therefore, this study aims to analyze the determinants of parental preventive behavior regarding diabetes mellitus in children. The research employed a cross-sectional study design and was analyzed using quantitative software. The study population consisted of parents with children aged 7–12 years in Jatilawang, with 99 respondents selected through stratified random sampling. Data were collected by measuring the children's weight and height, interviewing parents using structured questionnaires, and testing children's blood glucose levels. The data were then analyzed using univariate, bivariate, and multivariate statistical tests. The findings revealed a significant association between parental attitudes and preventive behaviors toward childhood diabetes (p-value = 0.019). Positive attitudes were reflected in practices such as providing nutritious meals, limiting sweetened and processed foods, supervising children's snack intake, encouraging physical activity, and ensuring regular health check-ups. In contrast, parental knowledge and income level were not significantly associated with preventive behaviors.